Research of Pathogens in Water and in Human Body using Resonance Laser Spectroscopy Techniques - Mogilnaya, T. Y.; Botikov, A. G.; Petelin, N. A.; Sheryshev, A. E. (New Trends in Physical Science Research Vol. 8, 2022)
Recent years have shown the importance of timely and rapid identification of various pathogens. A promising method is the IR spectroscopy method. The article is devoted to the monitoring of pathogens and nanomarkers in water and in the human body in real time.